PENGARUH SUHU PENGEMPAAN TERHADAP KARAKTERISTIK PAPAN PARTIKEL KAYU SENGON (FALCATARIA MOLUCCANA) DAN BAMBU WULUNG (GIGANTOCHLOA ATROVIOLACEA) - Hanif Gunawan, Muhammad
Bamboos are known as a fast-growing species that can be used as an alternative material to replace wood, but bamboo processing still produces a lot of waste that is not utilized. Bamboo waste can be used as raw material for particleboard. This study aims to determine the effect of compression temperature on the characteristics of particleboards made from sengon wood (Falcataria moluccana), a mixture of sengon wood and wulung bamboo, and wulung bamboo (Gigantochloa atroviolacea). Wettability test was carried out using Corrected Water Absorption Height method (CWAH) on sengon wood and wulung bamboo particles to determine the particle’s wettability properties. This study uses completely randomized design (CRD) on the characteristics of 3 types of boards based on the composition of the substrate weight (100% sengon wood (J1); 50% sengon wood and 50% wulung bamboo (J2); 100% wulung bamboo (J3)). Sengon wood (18 mesh) and wulung bamboo (6 mesh) particles were mixed with urea formaldehyde (15% dry weight of particles), then hot-pressed at 3 different compression temperatures (120oC (K1), 130oC (K2) and 140oC (K3)) with pressure level of 2 MPa for 10 minutes. Particleboards were tested for density, moisture content, thickness swelling, water absorption, MOE, MOR, IB and screw-holding strength according to JIS A 5908:2003 standard. The results were then statistically analyzed by ANOVA and Duncan's test. Wettability test showed that wulung bamboo had a higher wettability (130,04 cm) than sengon wood (91,16 cm).The results revealed that the pressing temperature had a significant effect on moisture content (5,56% - 9,62%), density (0,5 – 0,61 gr/cm3), water absorption (70,81% - 132,61% ), thickness swelling (8,44% - 17,38%), MOE (2053,96 – 7121,48 kg/cm2), MOR (10,69 – 116,39 kg/cm2) and IB (0,97 – 6,18 kg/cm2) on all particleboard, although not affecting the screw-holding strength significantly (26,4 – 48,59 kg). Particleboard pressed at 140oC complies with JIS A 5908:2003 type 8 standards except MOE, thus hot-pressing at 140oC helps to produce quality boards.